HUBUNGAN OPENNESS DAN CONSCIENTIOUSNESS TERHADAP PERILAKU KERJA INOVATIF: PERAN MODERASI DARI MASA KERJA PADA PERUSAHAAN STARTUP - Steffira Anjani; Eka Gatari (Jurnal Psikologi TALENTA, 2019)
Personality traits (openness and conscientiousness) were found to play a major role to improve innovative work behavior. However, the relationship between the two variables cannot be fully understood because of the rule of tenure as the moderator. In order to provide greater clarity, researcher wants to examine the effects of openness and conscientiousness on innovative work behavior and how the dynamic of moderating effects of tenure on the associations between traits and innovative work behavior among startup employees. Researcher has conducted a cross-sectional study on 105 startup employees. The results showed that openness and conscientiousness personality traits influenced the innovative work behavior, but there was no moderation effect of tenure to be found. Findings of this research can increase theoretical understanding and also can be used by startup companies in the recruitment and selection process to select employees who have the characteristics of openness and conscientiousness with high potential to innovate.